2004
DOI: 10.1117/12.563640
|View full text |Cite
|
Sign up to set email alerts
|

Parallel recording with optical waveguide array

Abstract: We present an analysis of the reading capability of a novel optical pickup consisting of a single-mode and a multi-mode rectangular waveguide. According to the simulations, if one has prior information about the structure of the disk, superresolution readout could be achieved. The proposed system has the advantage to be compact and should be straightforward to be extended to arrays. The working distance of this optical pickup can be adapted from near-to farfield by changing the length of the multi-mode wavegui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been shown that the resolution of the self-imaging effect in planar waveguides is about W λ / 4 , which is much smaller than the waveguide width W . This enables multimode waveguides to be used as focusing systems. , In planar waveguides, waveguide grating lenses have been used for focusing of visible light . Self-imaging in cylindrical waveguides was theoretically analyzed in ref .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the resolution of the self-imaging effect in planar waveguides is about W λ / 4 , which is much smaller than the waveguide width W . This enables multimode waveguides to be used as focusing systems. , In planar waveguides, waveguide grating lenses have been used for focusing of visible light . Self-imaging in cylindrical waveguides was theoretically analyzed in ref .…”
Section: Introductionmentioning
confidence: 99%